2014
DOI: 10.1136/injuryprev-2013-040964
|View full text |Cite
|
Sign up to set email alerts
|

An international review of the frequency of single-bicycle crashes (SBCs) and their relation to bicycle modal share

Abstract: ObjectivesTo study cyclists’ share of transport modes (modal share) and single-bicycle crashes (SBCs) in different countries in order to investigate if the proportion of cyclist injuries resulting from SBCs is affected by variation in modal share.MethodsA literature search identified figures (largely from western countries) on SBC casualties who are fatally injured, hospitalised or treated at an emergency department. Correlation and regression analyses were used to investigate how bicycle modal share is relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(66 citation statements)
references
References 32 publications
6
59
1
Order By: Relevance
“…Consistent with international data indicating that between 5% and 30% of cyclist fatalities are caused by single vehicle crashes,13 this study found this figure to be 12% in Australia. However, there is a proportional increase from only 3% in 1991 to almost one in every four fatal cyclist crashes in 2013.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with international data indicating that between 5% and 30% of cyclist fatalities are caused by single vehicle crashes,13 this study found this figure to be 12% in Australia. However, there is a proportional increase from only 3% in 1991 to almost one in every four fatal cyclist crashes in 2013.…”
Section: Discussionsupporting
confidence: 90%
“…In particular, the total number of single crashes is higher than the number of crashes between cyclists and pedestrians, according to police reports (NYC Department of Transportation, 2012; City of Boston, 2013; Department for Transport, 2013; Schramm, Rakotonirainy, & Haworth, 2010). Additionally, with reference to studies based on hospital and/or survey data (De Geus et al, 2012;Juhra et al, 2012;Malczyk, Bauer, Juhra, Schick, & Münster, 2014;Rizzi, Stigson, & Krafft, 2013;Schepers & den Brinker, 2011;Schepers & Wolt, 2012;Schepers et al, 2014) single bicycle crashes represent the majority of accidents which involve bicycle.…”
Section: Limitations Of the Studymentioning
confidence: 98%
“…While most bicycle accidents do not involve motorized vehicles (Amoros et al, 2012;Davidson, 2005;Scheiman et al, 2010;Tucci and Barone, 1988), collisions with motorized vehicles account for majority of the reported bicyclists' fatalities (Chong et al, 2010;Nicaj et al, 2009;Scheiman et al, 2010;Rosenkranz and Sheridan, 2003;Rowe et al, 1995). For serious injuries, bicycle accidents with motor vehicle involvement account for minority of MAIS3 injuries, and the literature is split for MAIS4+ injuries (Langley et al, 2003;Schepers et al, 2014). However, the proportions of serious injuries is higher in accidents between bicyclists and motorized vehicles compared to bicycle accidents not involving motorized vehicle (Langley et al, 2003;Sze et al, 2011).…”
Section: Introductionmentioning
confidence: 96%